Asal-Usul Masyarakat Maluku, Budaya dan Persebarannya: Kajian Arkeologi dan Mitologi - Wuri Handoko (Kapata Arkeologi, 2007)
Pursuant to archaeology study, origin socialize Moluccas can be identified to come from race with cultural characteristic of Austronesia, as does the other race inhabiting earth of this Nusantara. Mostly socialize Moluccas of pursuant to study of mytology trust that tribe inhabiting this Archipelago come from a sanctum in Seram Island, which then disseminate to entire all region of Moluccas islands, This Article try to study and discuss genesis of terms in Moluccas Islands on the basis of data of archaeology and mitology.